Using remote sensing to map in-field variability of peanut maturity - Santos, A. F. [UNESP]; Lacerda, L. N.; Gobbo, S.; Tofannin, A.; Silva, R. P. [UNESP]; Vellidis, G. (De Gruyter, 2019)
A study was conducted to assess if vegetation indices (VIs) could be used as indicators of peanut maturity. A 24 ha block of a rainfed field with clearly visible soil and crop variability was used. An unmanned aerial vehicle (UAV) equipped with a multispectral camera captured spectral reflectance from the peanut canopy. The reflectance data were used to evaluate several VIs as potential indicators of peanut maturity. Pearson's correlation and linear regression were used to evaluate the response of the VIs as well as the sensitivity of individual reflectance bands to peanut maturity. The red edge band was the most sensitive. The most responsive VIs were the non-linear index (NLI) and the modified non-linear index (MNLI) when red edge reflectance was substituted for red reflectance.
Keywords: Multispectral images; Red edge; Reflectance; UAV; Vegetation index